Synthetic and Antimicrobial Studies of Hexacoordinated Ternary Complexes of Mn(II) and Cu(II) - K. Agarwal, Suresh; Jaya Jain, (Ms.); Chand, Subhash (Asian Journal of Chemistry, 2010)
Some new ternary complexes of Mn(II) and Cu(II) with isonitrosoacetophenone isonicotinoyl hydrazone (INAPIH)/4-chloroisonitrosoacetophenone isonicotinoyl hydrazone (ClINAPIH) as primary and 1-(o-methoxy anilinomethyl) benzimidazole (MAMB) as secondary ligand have been synthesised and their structural features have been studied on the basis of analytical, spectral and conductance data. Analytical data suggest 1 : 1 : 1 (M-L/L´-L") stoichiometric composition for the isolated ternary complexes (where M = Mn2+/Cu2+, L = deprotonated INAPIH, L´ = deprotonated ClINAPIH and L" = MAMB). The complexes show 1 : 1 electrolytic nature. IR spectra confirm the tridentate and bidentate behaviour of the hydrazone (INAPIH/ClINAPIH) and Mannich base (MAMB) respectively. Electronic spectral data propose octahedral stereochemistry for the complexes. The complexes show increased antimicrobial activity than the corresponding ligands.